Effect of organic amendment derived from co-composting of chicken slurry and rice straw on reducing nitrogen loss from urea - Omar, Latifah; Haruna, Ahmed Osumanu; Nik Majid, Nik Muhamad (Taylor & Francis, 2016)
Co-composting of chicken slurry and rice straw with clinoptilolite zeolite and urea as additives was conducted to determine the characteristics of a compost and their effects on controlling ammonium (NH4+) and nitrate (NO3−) losses from urea. Quality of the compost was assessed based on temperature, moisture content, ash, pH, electrical conductivity, carbon/nitrogen (C/N) ratio, NH4+, NO3−, macronutrients, heavy metals, humic acid, microbial population, germination index, and phytotoxicity test. Moisture content and C/N ratio of the compost were 43.83% and 15, respectively. Total N, humic acid, ash, NH4+, NO3−, phosphorus (P), calcium (Ca), magnesium (Mg), potassium (K), and sodium (Na) increased after co-composting rice straw and chicken slurry. Copper, iron (Fe), manganese (Mn), zinc (Zn), and microbial biomass of the compost were low. The germination rate of Zea mays on distilled water and Spinacia oleracea growth on peat-based growing medium (PBGM) and compost were not significantly different. Urea amended with compost reduced N loss by retaining NH4+ and NO3− in the soil.